Der deutsche Leistungsbilanzüberschuss: Fluch oder Segen? - Michael Grömling; Jürgen Matthes; Heiko Peters; Philipp Harms; Gustav Horn; Fabian Lindner (Wirtschaftsdienst, 2016)
Deutschlands Leistungsbilanzüberschuss steht international in der Kritik. Er übersteigt deutlich die Zielvorgaben im Rahmen des Makroökonomischen Überwachungsverfahrens der Europäischen Union. Welche Ursachen die auseinanderlaufende Entwicklung der Exporte und Importe hat, wird allerdings sehr unterschiedlich interpretiert. Die einen sehen hier die Fortentwicklung von Basiseffekten einzelner außergewöhnlicher Jahre, andere vermuten eine zu geringe Binnennachfrage und eine aus verschiedenen Gründen deutliche Steigerung der Sparquote. In Zukunft dürfte allerdings die demografische Entwicklung in Deutschland die Leistungsbilanzüberschüsse schrumpfen lassen. – – Germany has one of the highest current account surpluses in the world. This is criticised by its global trading partners and is subject to the European Macroeconomic Imbalance Procedure. The authors interpret this phenomenon quite disparately. Some statethat the surplus is not the result of continuously and structurally slower imports relative to export growth. Instead, two periods of weak domestic demand have left lasting traces. This should not result in programmes to stimulate the demand side. Others, however, find that Germany should identify ways to increase its domestic demand, especially its public and private investment, in order to reduce its surplus. It is hard to exactly quantify and target an appropriate level of the current account, and thus political action should focus directly on the distortions and misallocations that potentially result from an imbalance. By 2020, however, the German surplus is likely to decrease due to demographic developments, the housing boom and slowing globalisation. Since the rotation of fixed income assets out of Europe ('Euroglut') is likely to continue, the outlook for the future value of the euro is therefore even more bearish.
Keywords: 330